Glossary of manufacturing process of peruvian wines - Castillo Farroñay, Zamia Ivón (2013)
In this paper we will present the collection of part of the lexicon related to the manufacturing process of the Peruvian wines in order to achieve a basic understanding of this topic. For data collection, it was considered necessary to develop a questionnaire whose application was carried out in some wineries located in the city of Lima. Once the necessary corpus was collected, it was systematized following different criteria stipulated by the Royal Spanish Academy (RAE) in the latest edition of the Dictionary of the Spanish Language.